Economic growth through gender parity: Evidence from education, labour, and governance in Uganda - Geoffrey Mubiinzi; Geoffrey Ssebabi Mutumba (Social Sciences and Humanities Open)
This study examines the extent to which gender parity in education, labour force participation, and governance influences Uganda's economic growth. It investigates whether progress in these dimensions of gender equality leads to sustained economic benefits by analysing both short- and long-run effects using an Autoregressive Distributed Lag (ARDL) model and annual data from 1997 to 2023. The results reveal contrasting effects: while educational parity has a positive but statistically insignificant long-run impact, suggesting that increased female enrolment alone is insufficient for economic transformation, labour force parity exerts a significant negative long-run effect due to structural inefficiencies, such as occupational segregation and under-employment. By contrast, governance parity, measured by female representation in parliament, demonstrates a significant short-run positive effect, indicating that inclusive decision-making can yield immediate economic gains, although its long-run effect remains statistically insignificant due to institutional constraints. These findings highlight the need for structural reforms to enhance the quality of female employment, institutional governance effectiveness, and the alignment between education and labour market demands. Policymakers should prioritize gender-sensitive policies that foster productive employment, strengthen governance reforms, and improve economic returns on educational parity to maximize the contribution of gender equality to economic growth. This study provides empirical evidence supporting gender-inclusive economic strategies, offering valuable insights for Uganda and similar economies in sub-Saharan Africa.